Short communication. Susceptibility of Phoenix theophrasti (Palmae: Coryphoideae) to Rhynchophorus ferrugineus (Coleoptera: Curculionidae) and its control using Steinernema carpocapsae in a chitosan formulation - Dembilio, Óscar; Karamaouna, F.; Kontodimas, D. C.; Nomikou, M.; Jaques, Josep A. (2017)
The invasive red palm weevil, Rhynchophorus ferrugineus Oliv. (Coleoptera: Curculionidae) is the most destructive pest of palms in the world. It has been reported on 19 palm species belonging to 15 different genera. The host status of the Cretan Date Palm, Phoenix theophrasti, remains unclear. Therefore, the present study was carried out to ascertain the host status of this protected palm species. Additionally, the efficacy of entomopathogenic nematodes in a chitosan formulation to control this pest in P theophrasti was assessed. Our results showed that healthy 4-yr-old P theophrasti palms were not infested by adult females after 9 days exposure in a population density of 3 adults per plant. However, infestation was successful when neonate larvae were artificially introduced in palms. Therefore, natural populations of P theophrasti could be at risk. Gummy secretion was observed in both naturally and forced infested palms indicating the existence of antibiosis in this species. Curative applications with the entomopathogenic nematode Steinernema carpocapsae in a chitosan formulation in early infested P theophrasti palms managed to reduce insect's activity and could help the palms to recover.